THE RELATIONSHIP BETWEEN SOCIAL MEDIA ADDICTION AND ACADEMIC PROCRASTINATION: A SYSTEMATIC LITERATURE REVIEW - Respati Wisanggeni; Herdi Herdi; Eka Wahyuni (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the relationship between social media addiction and academic procrastination among students through a systematic literature review guided by PRISMA. Article searches were conducted using the Publish or Perish application with three databases, namely Google Scholar, Scopus, and Semantic Scholar. Seven articles from various databases were qualitatively analyzed to identify the relationship between the two variables. The findings show that the majority of studies found a positive and significant relationship between the two variables, and factors such as perseverance and loneliness also strengthen this relationship. These findings have important implications for efforts to prevent academic procrastination in the educational environment.